2015
DOI: 10.1002/smll.201500027
|View full text |Cite
|
Sign up to set email alerts
|

The Sequence‐Specific Cellular Uptake of Spherical Nucleic Acid Nanoparticle Conjugates

Abstract: We investigated the sequence-dependent cellular uptake of spherical nucleic acid nanoparticle conjugates (SNAs). This process occurs by interaction with class A scavenger receptors (SR-A) and caveolae-mediated endocytosis. It is known that linear poly(guanine) (poly G) is a natural ligand for SR-A, and it has been proposed that interaction of poly G with SR-A is dependent on the formation of G-quadruplexes. Since G-rich oligonucleotides are known to interact strongly with SR-A, we hypothesized that SNAs with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
67
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 44 publications
1
67
1
Order By: Relevance
“…Previous work has shown that SNAs composed of G‐rich oligonucleotide sequences facilitate interactions with both cell‐surface scavenger receptors and a variety of serum proteins due to the enhanced formation of G‐quadruplexes, which is mediated by the dense layer of oligonucleotides that brings preoriented DNA strands in close proximity to one another on the SNA surface. Based upon the enhanced interaction of G‐quadruplex‐forming, G‐rich SNAs with serum proteins, we hypothesized that the protein corona formed on G‐rich SNAs would facilitate their uptake into phagocytic macrophage cells, and that this would lead to subsequent accumulation in the macrophage‐rich liver and spleen in vivo.…”
Section: Resultssupporting
confidence: 83%
“…Previous work has shown that SNAs composed of G‐rich oligonucleotide sequences facilitate interactions with both cell‐surface scavenger receptors and a variety of serum proteins due to the enhanced formation of G‐quadruplexes, which is mediated by the dense layer of oligonucleotides that brings preoriented DNA strands in close proximity to one another on the SNA surface. Based upon the enhanced interaction of G‐quadruplex‐forming, G‐rich SNAs with serum proteins, we hypothesized that the protein corona formed on G‐rich SNAs would facilitate their uptake into phagocytic macrophage cells, and that this would lead to subsequent accumulation in the macrophage‐rich liver and spleen in vivo.…”
Section: Resultssupporting
confidence: 83%
“…Taken together, the results indicate (1) distinct increases in cellular uptake of NPs driven by an increase in particle size; (2) a dependence on NP shape, where uptake of spherical particles was greater than that of nanostars of comparable surface area; and (3) the rates of cellular uptake increased after an initial 8-h period for larger particles, which is different from uptake kinetics previously reported for 13-nm AuNP-oligonucleotide conjugates, where the most rapid uptake occurred within the first 60 min. 40 …”
Section: Resultsmentioning
confidence: 99%
“…Cellular uptake of all constructs in major immune cell populations including pDCs, conventional dendritic cells (cDCs), B cells, NK cells, macrophages, and granulocytes was analyzed based on conventional surface markers by flow cytometry. Cellular uptake was quantified at 8 and 24 h time points, which were chosen because uptake was expected to have reached saturation by 8 h (based on previous SNA uptake studies using different cell lines) and internalized SNAs are predominately in endosomes . The 24 h time‐point was chosen to remain consistent with literature for comparison purposes; it is a treatment time that many labs use to evaluate immunological response …”
Section: Resultsmentioning
confidence: 99%